Aligned wet-electrospun starch fiber mats. (May 2019) - Wang, Hui; Kong, Lingyan; Ziegler, Gregory R.
Abstract: Electrospinning is a versatile technique to fabricate non-woven fiber mats with an average fiber diameter ranging from nanometers to micrometers. Fibers produced by electrospinning have potential application in numerous fields owing to their light weight, high surface area, and high porosity. In certain applications, anisotropic properties are desired, which may also improve mechanical strength. This study comprehensively documented the feasibility of directed fiber deposition in wet-electrospinning and offers an inexpensive setup for laboratory investigation. Aligned starch fiber mats were produced and the effects of three operational parameters, i.e., rotational speed, drum location, and coagulation bath composition, were evaluated. The alignment of starch fibers was affected by the ethanol concentration in the coagulation bath and drum rotational speed. Coherent fibers could be obtained in all trials except for the one at the lowest ethanol concentration (60% v/v) and highest rotational speed (500 rpm) when the drum was below the liquid. The tensile strength was influenced by the interaction of location and ethanol concentration, and that of rotational speed and ethanol concentration. This study set a promising example of making aligned biopolymer fiber mats and investigating fiber deposition in wet-electrospinning. Aligned starch fiber mats have potential applications in areas such as tissue engineering and as wound dressings. Graphical abstract: Image 104 Highlights: A benchtop setup for making aligned wet-electrospun fiber mats was developed. Effects of operational parameters in wet-electrospinning were evaluated. The tensile strength of fiber mat increased with fiber alignment.